2020
DOI: 10.1371/journal.pone.0235327
|View full text |Cite
|
Sign up to set email alerts
|

Videogame-related experiences among regular adolescent gamers

Abstract: The objective of this study was to identify the videogame-related experiences expressed by regular adolescent gamers and to explore the socio-family factors related to these experiences. A cross-sectional observational and descriptive study was carried out with a convenience sample of regular Spanish videogamers between 16 and 18 years old. To measure the use of videogames for evasion and its negative consequences, the Questionnaire of Videogame-Related Experiences (Cuestionario de Experiencias Relacionadas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Asimismo, el género masculino sostiene jugar entre cuatro y más de nueve horas tanto durante la semana como el fin de semana; sin embargo, el femenino lo hace entre cero y tres horas. Los resultados obtenidos referentes a un mayor uso de videojuegos por parte masculina van en línea con otras investigaciones y publicaciones, como las de Ponce-Blandón et al (2020) o Rubio (2017) a nivel estatal. En general, el uso de videojuegos está más relacionado con el género masculino, aunque esta preferencia parece atenuarse levemente con el paso del tiempo (Romrell, 2014).…”
Section: Discussionunclassified
“…Asimismo, el género masculino sostiene jugar entre cuatro y más de nueve horas tanto durante la semana como el fin de semana; sin embargo, el femenino lo hace entre cero y tres horas. Los resultados obtenidos referentes a un mayor uso de videojuegos por parte masculina van en línea con otras investigaciones y publicaciones, como las de Ponce-Blandón et al (2020) o Rubio (2017) a nivel estatal. En general, el uso de videojuegos está más relacionado con el género masculino, aunque esta preferencia parece atenuarse levemente con el paso del tiempo (Romrell, 2014).…”
Section: Discussionunclassified
“…By manipulating the game character, the young people feels present with the avatar, and through repeated imitation, learning, and recording of sports game knowledge, skills, and thinking, he or she integrates the avatar into his or her body schema and makes plans for different gaming scenarios to achieve his or her psychological [ 28 ]. As a form of virtual self-presentation, the visual image and behavioral performance of young peoples’ avatars in different e-gaming scenarios are highly variable, and young peoples’ perception of the visual image of their avatars and the behavioral meaning of their avatars is a key factor influencing their participation in sports fitness and sports competition [ 29 ]. Studies have shown that the interactive nature of sports e-Sports game scenarios provides a potential environment for young peoples’ social presence perceptions and that young peoples’ social presence perceptions mediate the relationship between e-Sports game scenarios and sport and fitness participation intentions.…”
Section: Hypothesis Of Research and Conceptual Modelmentioning
confidence: 99%
“…Video games are an integral part of the daily routine of young people, but at the same time, these games are popular and are played by users of all ages (Li, Wang, & Liu, 2020;Ponce-Blandón, et al, 2020;Barr & Copeland-Stewart, 2022). The ability of video games to entertain and intrigue their users has been proven in a modern technological society (Quwaider, Alabed, & Duwairi, 2019;Predescu & Mocanu, 2020;Heo & Park, 2021).…”
Section: Introductionmentioning
confidence: 99%